Measuring inorganic phosphate and intracellular pH in the healthy and hypertrophic cardiomyopathy hearts by in vivo 7T 31P-cardiovascular magnetic resonance spectroscopy - Valkovič, L; Clarke, WT; Schmid, AI; Raman, B; Ellis, J; Watkins, H; Robson, MD; Neubauer, S; Rodgers, CT (BioMed Central, 2019)
Background: Cardiovascular phosphorus MR spectroscopy (31P-CMRS) is a powerful tool for probing energetics in the human heart, through quantification of phosphocreatine (PCr) to adenosine triphosphate (ATP) ratio. In principle, 31P-CMRS can also measure cardiac intracellular pH (pHi) and the free energy of ATP hydrolysis (ΔGATP). However, these require determination of the inorganic phosphate (Pi) signal frequency and amplitude that are currently not robustly accessible because blood signals often obscure the Pi resonance.